Is subcutaneous laparoscopic recti abdominis repair (SCOLA) a safe approach to repair diastasis of the rectus abdominis muscles (DMRA)? A brief review - Coco, Danilo; Leanza, Silvana (Medical Studies/Studia Medyczne, 2022)
Diastasis of the rectus abdominis muscles is defined according to Beer’s classification: the distance between the straight abdominal muscles greater than 2.2 cm, measured 3 cm above the belly button with relaxed abdomen. The conditions in which it occurs most frequently are 12 months post-partum or in obese subjects who have suffered evident weight loss. We retrospectively evaluated PubMed databases, Embase, and the Cochrane Library by applying various combinations of the subject-related terms. The search terms identified with the medical subject heading (MeSH) were “diastasis of the rectus abdominis (DMRA), laparoscopic repair, subcutaneous laparoscopic recti abdominis repair”. The aim of the study was to describe laparoscopic techniques for the correction of combined ventral hernia with the plication of the diastasis of the rectus abdominis, muscle and to present the results.